Gabrielle Kissinger - Are countries ready for agricultural adaptation? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Keynote Session V - National adaptation plans (NAPs): What are the opportunities for CCAFS to truly influence policy? by Gabrielle Kissinger, Lexeme Consulting. Filmed at the annual Science meeting of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) from 7-11th April, San Lorenzo del Escorial, Spain. For more information visit the CCAFS website: http://www.ccafs.cgiar.org